Classical weight-four L-value ratios as sums of Calabi-Yau invariants - Philip Candelas, Xenia de la Ossa, Joseph McGovern (SciPost Physics)
We revisit the series solutions of the attractor equations of 4d $\mathcal{N}=2$ supergravities obtained by Calabi–Yau compactifications previously studied in [P. Candelas et al., J. High Energy Phys. 11, 032 (2021)]. While only convergent for a restricted set of black hole charges, we find that they are summable with Padé resummation providing a suitable method. By specialising these solutions to rank-two attractors, we obtain many conjectural identities of the type discovered in [P. Candelas et al., J. High Energy Phys. 11, 032 (2021)]. These equate ratios of weight-four special L-values with an infinite series whose summands are formed out of genus-0 Gromov–Witten invariants. We also present two new rank-two attractors which belong to moduli spaces each interesting in their own right. Each of these moduli spaces possess two points of maximal unipotent monodromy. One has already been studied by Hosono and Takagi, and we discuss issues stemming from the associated L-function having nonzero rank.